2004
DOI: 10.1160/th04-03-0178
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of post-thrombotic syndrome in patients with previous pulmonary embolism

Abstract: There is little information available about the true incidence of post-thrombotic syndrome (PTS) after pulmonary embolism (PE). The aim of this study was to investigate the incidence of PTS in patients with previous pulmonary embolism without concomitant ultrasonographically-detectable deep vein thrombosis (DVT). A retrospective cohort study was conducted at a single tertiary care centre, Cosenza, Italy. Forty-seven consecutive patients with proved PE without DVT within the previous 2 to 6 years, 45 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“… 17 Finally, we combined ‘signs of PTS’ with the ‘type of VTE’ factor, so as to prevent inappropriate interactions: post-thrombotic syndrome almost exclusively occurs in tandem with DVT, rather than with PE. 18 This leaves 12 factors in our reduced model.…”
Section: Methods and Analysismentioning
confidence: 99%
“… 17 Finally, we combined ‘signs of PTS’ with the ‘type of VTE’ factor, so as to prevent inappropriate interactions: post-thrombotic syndrome almost exclusively occurs in tandem with DVT, rather than with PE. 18 This leaves 12 factors in our reduced model.…”
Section: Methods and Analysismentioning
confidence: 99%
“…However, literature from other studies reported up to 80% incidence of PTS in patients presenting with distal (calf) DVT; thus suggesting that this type of DVT may be associated with a considerable risk of PTS development [52, 53]. Moreover, pulmonary embolism without concomitant ultrasonographically detectable DVT does not predispose patients to PTS [54]. …”
Section: Risk Factors Evident At the Time Or During Initial Treatmmentioning
confidence: 99%